Health Monitoring Bracelet based on Internet of Things and Website - Alif Razi, Muhamad; Rahayu, Fajar; Firdaus, Naufal (JAREE (Journal on Advanced Research in Electrical Engineering), 2025)
Human mortality rates in the healthcare sector are often attributed to delayed detection of critical health conditions. Vital signs, encompassing metrics like heart rate, blood oxygen levels, and body temperature, play a pivotal role in assessing one's health status and guiding medical interventions. Nevertheless, prevailing vital sign monitoring techniques have limitations, including mobility constraints and reliance on bulky, costly equipment. To address these challenges and enhance physicians' monitoring capabilities, technology-enabled remote sensor readings via the internet are indispensable. However, according to Kominfo, some healthcare facilities, notably in Indonesia, lack internet access, with 3,126 out of 10,133 hospitals and health centers reported as lacking it as of October 2020. To bridge this connectivity gap and enable remote patient monitoring even in internet-deficient settings, this paper presents the design of an Internet of Things (IoT)-based health monitoring bracelet. This innovative bracelet facilitates remote tracking of heart rate, blood oxygen levels, and body temperature. Notably, it can transmit sensor data to a designated website, even in the absence of internet connectivity. Users can conveniently access their measurement data through an intuitive and user-friendly website interface, making this solution a promising tool for enhancing healthcare monitoring, particularly in resource-constrained environments